Benzo‐Annulated Steroids: Synthesis of Octahydro‐indeno‐phenanthrenes by Formal [3+3] Cyclocondensation Reaction with 1, 3‐Bis[(trimethylsilyl)oxy]buta‐1, 3‐dienes. Issue 5 (17th May 2013) - Erben, Friedrich; Specowius, Verena; Wölfling, János; Schneider, Gyula; Langer, Peter
Abstract Octahydro‐indeno‐phenanthrenes, benzo‐annulated steroids, were prepared by formal [3+3] cyclocondensation reaction of 1, 3‐bis[(trimethylsilyl)oxy]buta‐1, 3‐dienes with the silyl enol ether of 16‐formylestrone methyl ether.